Patient acceptance of naloxone resulting from targeted intervention from community pharmacists to prevent opioid misuse and accidental overdose. Issue 4 (2nd October 2021) - Skoy, Elizabeth; Werremeyer, Amy; Steig, Jayme; Eukel, Heidi; Frenzel, Oliver; Strand, Mark
Abstract: Background: Community pharmacists are in a unique position to prevent opioid-related deaths through the provision of naloxone. However, for those identified as candidates for take-home naloxone, the acceptance rate remains low. Value would be gained from knowing what patient demographics and pharmacist actions are associated with increased patient acceptance of naloxone. Methods : Through a state-wide program, community pharmacists screened all patients receiving an opioid prescription for risk of opioid misuse and/or accidental overdose. Pharmacists prescribed and/or dispensed take-home naloxone to patients at elevated risk. Naloxone acceptance rates were stratified based on risk factors for misuse and overdose to determine which patients are most likely to accept naloxone. Patient acceptance of naloxone and risks were captured electronically. Results : Pharmacist-initiated naloxone recommendations based on risk screening resulted in a 5.81% take-home naloxone acceptance rate. Individuals that were taking multiple opioid medications were most likely to accept the naloxone (20.45%). Concurrent disease states or medications (COPD, concurrent anxiety/depression medication, concurrent sleep aid) were associated with a statistically significant increase in the rate of naloxone acceptance. Acceptance of take-home naloxone increased as a patient risk for opioid misuse and/or accidental overdose increased. Conclusion : Patient acceptance of naloxone at the community pharmacy level was notably higher compared to national naloxone dispensing rates when pharmacists implemented a patient screening and systematic risk-based approach to identify candidates in need of take-home naloxone.